Devadasi and their intimate partners: Dynamics of relationship - Janardhana Navaneetham; Manjula Basavarju; Mutharaju Arelingiah (Wolters Kluwer Medknow Publications, 2018)
Background: Devadasi practice is still prevalent in some parts of North Karnataka; most of the Devadasis get into sex work for their survival. During sex work, devadasis would get close to their customer, as they feel secure and emotionally satisfied. Objectives: The present study aims at understanding the Devadasi sex worker (DSW) and their intimate partners' (IPs) relationship and knowing the reasons for continuing the relationship even though they experience violence and abuse from their IP. Methods: Exploratory research design was adopted. Purposive sampling was used for the field visits. Data were gathered through personal interviews during field visits along with the counselors who were capacitated to deal with the relationship issues of DSWs and their IPs. Modified thematic analysis was used to analyze twenty field visit reports. Results: This study analyzed the quality and dynamics of the relationship between DSWs and their IP. DSWs and their IP define their relationship as "like marriage" without legal recognition. DSWs accept the violence from their IP as a symbol of love. Violence was identified as a key concern for the sex workers and is often acceptable in their relationship. Conclusion: The relationship between DSWs and their IPs needs to be understood before arriving at the care plan to deal with the relationship issues. There is an urgent need for developing an interventional model for the counselors and equip them to deal with the relationship issues of DSWs.